Toponimia hispano-latina medieval (crónicas y documentos) - Martínez Ortega, Ricardo (Euphrosyne: Revista de filología clássica, 2015)
Various dubious toponyms in various medieval chronicles and documents are presented. The author applies the intrinsic and extrinsic study to each of them until reaching the identification and location of these toponyms; etymological aspects are also included.